DIGITAL MARKETING EFFECTIVENESS, PERCEIVED TRUST, AND YAMAHA MOTORCYCLE PURCHASE DECISIONS - Yenni Daud; Johannes Baptista Halik; Kordiana Sambara (Institute of Research and Community Outreach - Petra Christian University, 2026)
This study addresses the growing challenge of converting digital marketing exposure into actual purchasing decisions in the motorcycle industry, where consumer trust remains a critical issue. The research focuses on the role of perceived trust in linking digital marketing activities with Yamaha motorcycle purchase decisions. The objective of this study is to examine how digital marketing contributes to purchasing decisions through the mediation of perceived trust. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) based on data collected from 80 Yamaha motorcycle users in Makassar through an online questionnaire. The results indicate that digital marketing significantly strengthens perceived trust, while perceived trust plays a decisive role in shaping purchasing decisions. The direct relationship between digital marketing and purchasing decisions is weak; however, digital marketing indirectly contributes to purchasing decisions through perceived trust, indicating a full mediation effect. These findings highlight that trust-oriented digital marketing strategies are essential for influencing consumer purchasing behavior in high-involvement products.